Circular RNA circNF1 siRNA Silencing Inhibits Glioblastoma Cell Proliferation by Promoting the Maturation of miR-340 - Liu, Li; Jia, Li; Shao, Jun; Liu, Hanhua; Wu, Qinke; Wu, Xudong (Frontiers in Neurology, 2021)
It has been reported that circular RNA circNF1 promotes gastric cancer. This study aimed to analyze the role of circNF1 in glioblastoma (GBM). Expression of circNF1, mature miR-340, and miR-340 precursor in paired GBM and non-cancer tissues from GBM patients (n=50) was analyzed by RT-qPCR. GBM cells were transfected with circNF1 siRNA, followed by analyzing the expression of mature miR-340 and miR-340 precursor to study the effects of circNF1 knockdown on miR-340 maturation. CCK-8 assay was carried out to explore the effects of circNF1 and miR-340 on GBM cell proliferation. CircNF1 expression was upregulated in GBM and correlated with patient’s survival. In glioma tissues, circNF1 was inversely correlated with mature miR-340, but not miR-340 precursor. In GBM cells, circNF1 siRNA silencing upregulated mature miR-340, but not miR-340 precursor. Cell proliferation assay showed that circNF1 siRNA silencing and miR-340 overexpression decreased GBM cell proliferation. In addition, miR-340a inhibitor suppressed the effect of circNF1 siRNA silencing on cell proliferation. Therefore, circNF1 siRNA silencing might inhibit GBM cell proliferation by promoting miR-340 maturation.